Retrospective cohort of COVID-19 in patients with anti-CD20 treatment - Nieminen, Valtteri (My University, 2023)
Abstract Background: Anti-CD20 monoclonal antibodies are applied in a variety of autoimmune disorders and malignant diseases. Treatment with these agents causes a depletion in peripheral B-cells and loss of several B-cell functions, which typically last up to 9 – 12 months. Use of these monoclonal antibodies is associated with poor outcomes of COVID-19. With this study, we aim to study the risk and outcomes of prolonged COVID-19 in patients who had received anti-CD20 treatment prior to COVID-19. Methods: All adult patients of Turku University Hospital, Turku, Finland, who were diagnosed with COVID-19 between 1.1.2020 and 1.9.2022 and who had received anti-CD20 monoclonal antibodies within 12 months prior to COVID-19 diagnosis were included in this retrospective study. Results: 40 patients met the inclusion criteria. The patients median age was 64 years and 19 (47.5 %) were female gender. The median age was 64 years (interquartile range 55 – 75 years). 8 patients (20%) required intensive care and 10 (25%) died. 25 patients (64%) were admitted for COVID-19 within the first 14 days of symptoms, 12 (30%) were first admitted later within the first 30 days and 2 (5%) were first admitted for COVID-19 more than 30 days from onset of symptoms. A phenotype of prolonged pulmonary COVID-19, defined as respiratory symptoms, positive SARS-CoV-2 PCR, and interstitial pattern in high resolution computed tomography after 2 months from the onset of symptoms was observed in 7 patients (17.5%). Of those 7, 2 died due to COVID-19. In 2 cases of prolonged COVID-19, a short course of antiviral medication (remdesivir or ritonavir-boosted nirmatrelvir) in combination with antibody treatment directed against SARS-CoV-2 (tixagevimab-cilgavimab), resulted in prompt resolution of symptoms and clinical parameters. Discussion: Anti-CD20 treatment is associated with a phenotype of prolonged COVID-19, suggestive for sustained viral replication. These patients may benefit from a combination of antiviral medication and monoclonal antibody therapy directed against SARS-CoV-2.